Further Results about a Special Fermat-Type Difference Equation - Hongwei Ma; Jianming Qi; Zhenjie Zhang (Journal of Function Spaces)
In this paper, we prove the difference equation Fz3+ΔcFz+c3=1 does not have meromorphic solution of finite order over the complex plane C. We also discuss an application to the unique range set problem.